Além do caixa: memória e cotidiano do Mercado Municipal de São Miguel Paulista - Fornazeiro, Luisa Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O projeto pretende registrar, através da fotografia, a rotina dos comerciantes do Mercado Municipal de São Miguel Paulista, na cidade de São Paulo, SP. Para isso, será feita uma pesquisa sobre o histórico da região, e o papel e a relevância dos mercados públicos na conservação de histórias e tradições. A partir disso, serão feitas entrevistas com os comerciantes, a fim de adquirir repertório para o desenvolvimento de conceitos que conduzirão a curadoria das imagens registradas no local, bem como o desenvolvimento de uma identidade visual do projeto. O objetivo é desenvolver um projeto fotográfico documental que sirva de registro histórico e artístico, e que valorize o cotidiano e a vida das pessoas que trabalham no mercado.

The project aims to record, through photography, the routine of traders at the Municipal Market of São Miguel Paulista, in the city of São Paulo, SP. To this end, research will be carried out on the history of the region, and the role and relevance of public markets in the conservation of histories and traditions. From this, interviews will be carried out with traders, in order to acquire a repertoire for the development of concepts that will lead to the curation of images recorded on site, as well as the development of a visual identity for the project. The objective is to develop a documentary photographic project that serves as a historical and artistic record, and that values ​​the daily lives and lives of people who work in the market.
Beyond the cashier: memory and daily life at the Municipal Market of São Miguel Paulista
Keywords: Design editorial; Fotografia; Fotografia documental; Memória gráfica; Mercado público; São Miguel Paulista; Identidade Visual; Editorial design; Visual Identity; Graphic memory; Documentary Photography